Neuroimaging in Functional Neurological Disorder: State of the Field and Research Agenda - Perez, David L; Nicholson, Timothy R; Asadi-Pooya, Ali A; Bègue, Indrit; Butler, Matthew; Carson, Alan J; David, Anthony S; Deeley, Quinton; Diez, Ibai; Edwards, Mark J; Espay, Alberto J; Gelauff, Jeannette M; et al. (NeuroImage. Clinical, 2021)
Functional neurological disorder (FND) was of great interest to early clinical neuroscience leaders. During the 20th century, neurology and psychiatry grew apart - leaving FND a borderland condition. Fortunately, a renaissance has occurred in the last two decades, fostered by increased recognition that FND is prevalent and diagnosed using "rule-in" examination signs. The parallel use of scientific tools to bridge brain structure - function relationships has helped refine an integrated biopsychosocial framework through which to conceptualize FND. In particular, a growing number of quality neuroimaging studies using a variety of methodologies have shed light on the emerging pathophysiology of FND. This renewed scientific interest has occurred in parallel with enhanced interdisciplinary collaborations, as illustrated by new care models combining psychological and physical therapies and the creation of a new multidisciplinary FND society supporting knowledge dissemination in the field. Within this context, this article summarizes the output of the first International FND Neuroimaging Workgroup meeting, held virtually, on June 17th, 2020 to appraise the state of neuroimaging research in the field and to catalyze large-scale collaborations. We first briefly summarize neural circuit models of FND, and then detail the research approaches used to date in FND within core content areas: cohort characterization; control group considerations; task-based functional neuroimaging; resting-state networks; structural neuroimaging; biomarkers of symptom severity and risk of illness; and predictors of treatment response and prognosis. Lastly, we outline a neuroimaging-focused research agenda to elucidate the pathophysiology of FND and aid the development of novel biologically and psychologically-informed treatments.
Keywords: DTI; MRI; neurozobrazování; konverzní poruchy; Functional neurological disorder; lidé; Neuroimaging; Nervous System Diseases; Humans; Conversion Disorder; nemoci nervového systému; Conversion disorder; fMRI